2015
DOI: 10.1007/s00335-015-9603-x
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies for mutation detection in phenotype-driven screens utilising next generation sequencing

Abstract: Mutagenesis-based screens in mice are a powerful discovery platform to identify novel genes or gene functions associated with disease phenotypes. An N-ethyl-N-nitrosourea (ENU) mutagenesis screen induces single nucleotide variants randomly in the mouse genome. Subsequent phenotyping of mutant and wildtype mice enables the identification of mutated pathways resulting in phenotypes associated with a particular ENU lesion. This unbiased approach to gene discovery conducts the phenotyping with no prior knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 75 publications
0
24
0
1
Order By: Relevance
“…However, it is still a challenge for clinicians to obtain a precise molecular diagnosis using conventional genetic methods because of the clinical and genetic heterogeneity of this disorder. Recently, targeted NGS technology is emerging as a powerful genetic tool and has been successfully used to identify causal genes in various genetic disorders (Simon et al, 2015). In the present study, we used targeted NGS of 270 neuromuscular disease-associated genes and identified two novel LAMA2 mutations in a Chinese patient with MDC1A.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still a challenge for clinicians to obtain a precise molecular diagnosis using conventional genetic methods because of the clinical and genetic heterogeneity of this disorder. Recently, targeted NGS technology is emerging as a powerful genetic tool and has been successfully used to identify causal genes in various genetic disorders (Simon et al, 2015). In the present study, we used targeted NGS of 270 neuromuscular disease-associated genes and identified two novel LAMA2 mutations in a Chinese patient with MDC1A.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have had some success in combining forward mutagenesis, QTL mapping, and next generation sequencing to identify mutations in individual mouse genes that impact complex behavioral traits (Andrews et al 2012; Funato et al 2016; Gallego-Llamas et al 2015; Ha et al 2015; Hossain et al 2016; Kumar et al 2011; Militi et al 2016; Simon et al 2015), and while other approaches are also effective, there will likely be an important role for this screening approach in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The process would only declare phenotypes that were heritable, and would simultaneously display the causative mutation along with information about the affected protein. This “instant positional cloning” method was a tremendous breakthrough, as it allowed the resolution of phenotype in real time (45;46). Phenotypes could be solved as quickly as they were detected.…”
Section: The Golden Age Beginsmentioning
confidence: 99%